2020
DOI: 10.1016/j.psj.2020.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Chondronecrosis with osteomyelitis in broilers: further defining lameness-inducing models with wire or litter flooring to evaluate protection with organic trace minerals

Abstract: The feed additive Availa-ZMC was investigated for the ability to reduce lameness in broilers using 2 alternative models for inducing lameness. The mixture of organic trace minerals was effective in reducing lameness by 20% in the wire flooring model and 25% in the litter flooring model with the bacterial challenge. Lameness in both models is overwhelmingly attributable to bacterial chondronecrosis with osteomyelitis. The reduction in lameness was associated, at least in part, with enhanced intestinal barrier i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 32 publications
(24 reference statements)
2
29
0
Order By: Relevance
“…We performed ELA with different bacterial isolates isolated from lame broilers to estimate relative pathogenicity. We observed that S. agnetis 908 is not pathogenic in the ELA even though we have shown that this isolate readily infects young broilers when administered at 10 4 or 10 5 CFU/ml in drinking water at 20 and 21 days of age (1, 3, 6, 7). Broilers challenged with S. agnetis 908 begin to develop lameness by 41 days of age and by 56 days of age 50% of the birds will be clinically lame with BCO lesions in proximal femoral and tibial heads.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…We performed ELA with different bacterial isolates isolated from lame broilers to estimate relative pathogenicity. We observed that S. agnetis 908 is not pathogenic in the ELA even though we have shown that this isolate readily infects young broilers when administered at 10 4 or 10 5 CFU/ml in drinking water at 20 and 21 days of age (1, 3, 6, 7). Broilers challenged with S. agnetis 908 begin to develop lameness by 41 days of age and by 56 days of age 50% of the birds will be clinically lame with BCO lesions in proximal femoral and tibial heads.…”
Section: Discussionmentioning
confidence: 85%
“…We therefore assessed different BCO isolates at 10 5 and 10 6 CFUs (Table 1). We included S. agnetis 908 recovered from a femoral BCO lesion on our research facility as this isolate can induce lameness ≥50% by day 56 when administered in drinking water for two days to 20-day old broilers (1, 3, 6, 7). Surprisingly, 908 injections of even 10 6 CFUs resulted in only 14% embryo lethality, a level not statistically different from 1xPBS control treatment (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The predominant species was Staphylococcus cohnii (~95%) with 3-4% Staphylococcus lentus and 1-2% E. coli . Air sampling during our broiler experiments at the University of Arkansas Poultry Research farm typically identify predominantly S. cohnii but not E. coli (26, 27).…”
Section: Resultsmentioning
confidence: 99%